PERAN PENYULUH DALAM PEMBERDAYAAN POKLAHSAR RUMPUT LAUT DI KELURAHAN TANJUNG TENGAH KABUPATEN PENAJAM PASER UTARA - Ramlah; Fitriyana; Etik Sulistiowati Ningsih (Jurnal Pembangunan Perikanan dan Agribisnis, 2018)
This Research aim to grasp the role of extension in empowerment the POKLAHSAR “Swakarya Bersama” and to grasp the rate of empowerment on POKLAHSAR “Swakarya Bersama”. This research was conducted in Tanjung Tengah Regency of Penajam Paser Utara since January to February 2017. This research census sampling method which is the number of samples was 10 people. The data used are primary and secondary data, primary data was collected using a survey method through a questionnaire. Data were analyzed using qualitative research method, that are descriptive and Likert Scale measurement method using 4 indicators of the role of extension and 4-level indicators of empowerment.The results of this study indicated that the average scale for 4 indicators of the role of extension worker is 37,9, which means that the role of extension worker is highly influence on POKLAHSAR “Swakarya Bersama” ‘s empowerment. Meanwhile, the average scale of POKLAHSAR member empowerment for 4 empowerment level indicator is 56,7, it could be categorized as high level.